Thyroid Function after Subtotal Thyroidectomy in Patients with Graves’ Hyperthyroidism - E. J. Limonard; P. H. Bisschop; E. Fliers; E. J. Nieveen van Dijkum (The Scientific World Journal)
Background. Subtotal thyroidectomy is a surgical procedure, in which the surgeon leaves a small thyroid remnant in situ to preserve thyroid function, thereby preventing lifelong thyroid hormone supplementation therapy. Aim. To evaluate thyroid function after subtotal thyroidectomy for Graves’ hyperthyroidism. Subjects and Methods. We retrospectively reviewed the medical records of all patients (𝑛=62) who underwent subtotal thyroidectomy for recurrent Graves’ hyperthyroidism between 1992 and 2008 in our hospital. Thyroid function was defined according to plasma TSH and free T4 values. Results. Median followup after operation was 54.6 months (range 2.1–204.2 months). Only 6% of patients were euthyroid after surgery. The majority of patients (84%) became hypothyroid, whereas 10% of patients had persistent or recurrent hyperthyroidism. Permanent recurrent laryngeal nerve palsy and permanent hypocalcaemia were noted in 1.6% and 3.2% of patients, respectively. Conclusion. In our series, subtotal thyroidectomy for Graves’ hyperthyroidism was associated with a high risk of postoperative hypothyroidism and a smaller, but significant, risk of persistent hyperthyroidism. Our data suggest that subtotal thyroidectomy seems to provide very little advantage over total thyroidectomy in terms of postoperative thyroid function.